Cystathionine β-synthase affects organization of cytoskeleton and modulates carcinogenesis in colorectal carcinoma cells - Liskova, Veronika; Chovancova, Barbora; Babula, Petr; Rezuchova, Ingeborg; Pavlov, Kristina Ploth; Matuskova, Miroslava; Krizanova, Olga (Frontiers in Oncology, 2023)
Background Cystathionine β-synthase (CBS), one of three enzymes that endogenously produce hydrogen sulfide, is extensively studied for its relevance in the cells of various tumors. In our previous work, we observed that the immunofluorescence pattern of CBS is very similar to that of tubulin and actin. Therefore, we focused on the potential interaction of CBS with cytoskeletal proteins β-actin and β-tubulin and the functional relevance of the potential interaction of these proteins in colorectal carcinoma cell lines. Methods To study the potential interaction of CBS with cytoskeletal proteins and its functional consequences, a CBS-knockout DLD1 (DLDx) cell line was established by using the CRISPR/Cas9 gene editing method. The interaction of the selected cytoskeletal protein with CBS was studied by immunoprecipitation, Western blot analysis, immunofluorescence, and proximity ligation assay. The functional consequences were studied by proliferation and migration assays and by generation of xenografts in SCID/bg mice. Results We have found that CBS, an enzyme that endogenously produces H2S, binds to cytoskeletal β-tubulin and, to a lesser extent, also to β-actin in colorectal carcinoma-derived cells. When CBS was knocked out by the CRISPR/Cas9 technique (DLDx), we observed a de-arranged cytoskeleton compared to the unmodified DLD1 cell line. Treatment of these cells with a slow sulfide donor GYY4137 resulted in normal organization of the cytoskeleton, thus pointing to the role of CBS in microtubule dynamics. To evaluate the physiological importance of this observation, both DLD1 and DLDx cells were injected into SCID/bg mice, and the size and mass of the developed xenografts were evaluated. Significantly larger tumors developed from DLDx compared to the DLD1 cells, which correlated with the increased proliferation of these cells. Conclusions Taken together, in colorectal cancer DLD1 cells, CBS binds to the cytoskeleton, modulates microtubule dynamics, and thus affects the proliferation and migration in the colorectal carcinoma stable cell line.